The Practice of Implementing Aqiqah by Buying Ready Stock in Bajenis Subdistrict, Tebing Tinggi City in the View of Syafi'i's School - Muhammad Syukri Albani Nasution; Ramadhan Syahmedi Siregar; Nurul Arif El Hakim (Budapest International Research and Critics University, 2020)
The aim of this study to find out the practice of implementing Aiqaah by buying ready stock in Bajenis district. The approach used in this study is a qualitative approach. The result of the study shows that there is no intention of aqiqah at the time of slaughtering animals. Meanwhile, according to the Syafi'i mazhab, when the aqiqah animal is slaughtered, it must be intended for the aqiqah of the child. Communities in Bajenis district does not know anything about the shape of the aqiqah animal, whether the meat of the animal purchased in the market has a defect or not. Meanwhile, according to the Syafi'i mazhab, aqiqah animal must be protected from disgrace or disability. Regarding the problem of the dose of aqiqah animal, the community in Bajenis district , no longer refer to Islamic rules especially according to the Syafi'i school of thought and it is not known whether the meat comes from the same animal or has been mixed with other animal meat which is also sold by the market traders. In addition, it is not known whether the animal is old enough or not. Meanwhile, according to the Shafi'i school, the measure of aqiqah animal is two for boys and one for girls and if the animal is a camel, then it is at least five years old, if the animal is a cow, then at least two years old, if the animal is a goat, then at least one year old.